Rearrangement of allyl phenyl ether over Al-MCM-41 - Mathew, Nevin T.; Khaire, S.; Mayadevi, S.; Jha, Ratnesh Kumar; Sivasanker, S. (Journal of Catalysis, 2005)
Claisen rearrangement of allyl phenyl ether to o-allylphenol and a dihydrobenzofuran derivative was investigated over MCM-41 with different Si/Al ratios. Higher aluminum content, higher reaction temperatures, and longer run duration favor the formation of the ring compound 2,3-dihydro-2-methyl benzofuran. There is a close relationship between acidity and conversion, which suggests that the reaction occurs inside the large pores of MCM-41. The influence of temperature and catalyst Si/Al ratio on the reaction are examined by kinetic analysis, under the assumption of a first-order consecutive reaction. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: Al-MCM-41; allyl phenyl ether; Claisen rearrangement; Mesoporous material; molecular rearrangement; Solid acids

Adsorption of methanol on Si(100)/SiO(2)and mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Ravi, V.; Jacob, Nalini E.; Patil, K. R. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
Adsorption of methanol on SiO(100)/SiO2 substrate and mesoporous SBA-15 has been studied by using Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). Contact angle technique is employed to study the adsorption kinetics of methanol on SiO(100)/SiO2 and thermal stability of adlayer. Thermogravimetric (TGA) technique is used to understand the thermal behavior of methanol layer on SBA-15. Adsorption kinetics fit fairly well with Langmuir isotherms giving adsorption rate constant, k(a) = 0.0021 W s(-1). FTIR results show formation of methoxy silicon (SiOCHA silicon polyhydride (SiH2), carboxylate, molecular water and hydroxyl groups on Si(100)/SiO2 surface and only methoxy silicon on SBA-15. XPS results confirm methanol adsorption and support FTIR results. The methanol adlayers are found to be thermally stable up to a temperature of similar to 262 degrees C on both Si(100)/SiO2 and SBA-15 and decompose between 262 and 450 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; desorption; kinetics; Methanol; SBA-15; Si(100)/SiO2; thermal stability

Adsorption of methanol on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B. (Materials Letter, 2007)
The adsorption of methanol onmesoporous SBA-15 has been studiedbyrising Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray photoclectrom spectroscopy (XPS) and tbennogravimettic analysis (TGA). The BET surface area analysis shows decreases of the surface area from 387 to 383 m(2)/g, pore volume from 0.88 to 0.81 cm(3)/g and pore diameter from 9.07 to 8.4 mm after methanol adsorption. The appearance of strong IR bands at 2862 and 2964cm(-1) due to methyl (-CH3) symmetric and asymmetric stretching demonstrate the presence of methanol and evidence of successful methanol adsorption. XPS results show increase of carbon and oxygen content on the surface of SBA-15. Thermogravirriettic analysis shows that the methanol adsorbed on SBA-15 is stable up to a temperature of 265 degrees C and that the methanol adlayers decompose between 265 and 588 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Electron microscopy; Methanol; SBA-15; Surfaces; thermal stability

Synthesis and characterization of novel polyurethanes based on 4,4 `-[1,4-phenylenedi-diazene-2,1-dlyl] bis(2-carboxyphenol) and 4,4 `-[1,4-phenylenedi-diazene-2,1-diyl] bis(2-chlorophenol) hard segments - Raghu, A. V.; Gadaginamath, G. S.; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Reactive & Functional Polymers, 2007)
Eight novel polyurethanes (PUs) based on 4,4'-[1,4-phenylenedi-diazene-2,1-diyl]bis(2-carboxyphenot) and 4,4'-[1,4phenylenedi-diazene-2,1-diyl]bis(2-chloro- phenol) as hard segments with four diisocyanates viz., 4,4-diphenyl-methane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate were prepared. Structural and thermal characterization of the segmented PUs were determined by FT-IR, UV spectrophotometry, fluoroscence spectroscopy, H-1 NMR, C-13 NMR spectroscopy and DTA/TGA analysis. All the PUs contain domains of semi-crystalline and amorphous structures, as indicated by X-ray diffraction. PUs were soluble in polar aprotic solvents like N-methyl-2-pyrrolidone (NMP), dimethyl formamide (DMF) and dimethylsulfoxide (DIVISO). (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: azo polymers; fluorescence; hard segments; Morphology; phase separation; polyurethanes; spectroscopy; Thermal properties

Synthesis, characterization, and acoustic properties of new soluble polyurethanes based on 2,2 `-[1,4-phenylenebis(nitrilomethylylidene)diphenol and 2,2 `-[4,4 `-methylene-di-2-methylphenylene-1,1 `-bis(nitrilomethylylidene)]diphenol - Raghu, A. V.; Gadaginamath, G. S.; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
Eight novel polyurethanes based on 2,2'-[1,4-phenylenebis(nitrilomethylylidene)]diphenol and 2,2-[4,4'methylene-di-2-methylphenylene-1,1'-bis(nitrilomethylylidene) ]diphenol acting as hard segments with two aromatic and two aliphatic diisocyanates (4,4'-diphenytmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate) were prepared and characterized with Fourier transform infrared, UV spectrophotometry, fluorescence spectroscopy, H-1-NMR and C-13-NMR spectroscopy, thermogravimetric analysis, and differential thermal analysis. All the polyurethanes contained domains of semicrystalline and amorphous structures, as indicated by X-ray diffraction. The acoustic properties and solubility parameters were calculated with the group contribution method. (c) 2007 Wiley Periodicals, Inc.
Keywords: infrared spectroscopy; NMR; phase behavior; polyurethanes; Thermal properties

Inorganic-organic hybrid materials based on functionalized silica and carbon: a comprehensive understanding toward the structural property and catalytic activity difference over mesoporous silica and carbon supports - Bordoloi, Ankur; Mathew, Nevin T.; Lefebvre, F.; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2008)
Inorganic-organic hybrid materials based on functionalized silica and carbon were synthesized by anchoring molybdovanadophosphoric acid (H-5[PMo10V2O40]center dot 32.5H(2)O) onto amine-functionalized SBA-15, ethane-bridged SBA-15 and mesoporous carbon, respectively. Small angle X-ray diffraction, N-2 sorption analysis, HRTEM, SEM, IFT-IR, CP-MAS NMR were used to diagnose the mesoporous structure of inorganic-organic hybrid materials. The structural integrity of molybdovanadophosphoric acid has been found to be retained after immobilization over mesoporous materials. These inorganic-organic hybrid materials were tested in the environmentally friendly oxidation of 2-methylnaphthalene (2MN) with 30%, aqueous hydrogen peroxide. Molybdovanadophosphoric acid containing mesoporous organosilica hybrid material (ethane-bridged SBA-15) exhibited higher catalytic activities in the oxidation of 2MN to give a clean product 2-methy-1,4-naphthoquinone (menadione vitamin K3 precursor), because of the improved hydrophobicity of the material. The correlation between structural properties and catalytic activities of these hybrid materials has been well addressed in our present studies. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: 2-Methylnaphthalene; inorganic-organic hybrid materials; mesoporous carbon; mesoporous organosilica; Oxidation

Synthesis and characterization of novel schiff base polyurethanes - Raghu, A. V.; Gadaginamath, G. S.; Jeong, Han Mo; Mathew, Nevin T.; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2009)
Eight different types of novel polyurethanes (PUs) were synthesized through the polyaddition reaction of 4,4'-(ethane-1,2-diylidenedinitrilo)diphenol and 4,4'(pentane-1,5-diylidenedinitrilo)diphenol with four different diisocyanates: 4,4'-diphenylmethane diisocyanate, toluene 2,4-diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate. The resulting PUs were soluble in polar, aprotic solvents. Structures of the diols and PUs were established with Ultraviolet-visible, fluorescence, Fourier transform infrared (FTIR), (1)H-NMR, and (13)C-NMR spectroscopy data. FTIR and NMR spectral data indicated the disappearance of both hydroxyl and isocyanate groups in the PUs. The thermal properties were investigated with thermogravimetry and differential scanning calorimetry. The weight losses, glass transitions, onset temperatures, and crystalline melting temperatures were measured. All the PUs exhibited semicrystalline and amorphous morphologies, as indicated by X-ray diffraction. (C) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 113: 2747-2754, 2009
Keywords: amorphous; Morphology; polyurethanes; synthesis; Thermal properties